ON SOME SYSTEMS OF AESTHETIC CATEGORIES - MOUTSOPOULON, EVANGHELOS (Universidad Autónoma de Nuevo León, 2021)
If 1. an object in general is what constitutes for the human consciousness an exterior al of reference,and 2. an aesthetic object, natural or artistic, is what may effect an aesthetic emotion.and 3. an aesthetic object can receive, beyond any emotional appreciation, a rational appreciation and the attribution of meaning and of value such that the intentionality of human consciousness is objectified,then, the elucidation of a whole axiology of the aesthetic object is possible.THIS ELUCIDATION of aesthetic objects is made through categories, i.e., through very general classes of appreciative notions. These general classes of notions are of the type Plato speaks of in the Sophist as the highest genera or kinds (megista gené).